2016
DOI: 10.1007/s00294-016-0661-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic transcriptional memory

Abstract: Organisms alter gene expression to adapt to changes in environmental conditions such as temperature, nutrients, inflammatory signals and stress (Gialitakis et al. 2010; Conrath 2011; Avramova 2015; Solé et al. 2015; Ho and Gasch 2015; Bevington et al. 2016; Hilker et al. 2016). In some cases, organisms can “remember” a previous environmental condition and adapt to that condition more rapidly in the future (Gems and Partridge 2008). Epigenetic transcriptional memory in response to a previous stimulus can produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 48 publications
2
104
0
1
Order By: Relevance
“…There are numerous previous studies in plants and animals that defined hit‐and‐run mechanisms which reprogram loci for transcriptional activation . We suspected that similar mechanisms might be at work in memory T cells and, therefore, used mouse T cell models to investigate this.…”
Section: Inducible Factors Establish Immunological Memory By a Hit‐anmentioning
confidence: 99%
“…There are numerous previous studies in plants and animals that defined hit‐and‐run mechanisms which reprogram loci for transcriptional activation . We suspected that similar mechanisms might be at work in memory T cells and, therefore, used mouse T cell models to investigate this.…”
Section: Inducible Factors Establish Immunological Memory By a Hit‐anmentioning
confidence: 99%
“…Remarkably, LGA-HUAEC showed overexpression of GPX1 mRNA in response to H 2 O 2 treatment, compared with control, resembling the Epigenetic Transcriptional Memory (ETM) described in immune cells exposed to inflammatory mediators (D´Urso & Brickner, 2016;Gialitakis, Arampatzi, Makatounakis, & Papamatheakis, 2010). The ETM has been defined as an inducible gene overexpression when the same gene has been previously exposed to the same stimuli (Gialitakis et al, 2010;Light et al, 2013) If we consider the previously reported pro-oxidant environment in LGA fetuses from women with pregestational obesity (Catalano & Shankar, 2017;Malti et al, 2014), it is reasonable to ponder that oxidative response genes in LGA-derived HUAEC have been chronically stimulated during pregnancy, causing an epigenetic effect that can be mitotically inherited to cellular progeny.…”
Section: Brigeliusmentioning
confidence: 54%
“…Retaining an epigenetic memory of past incidents is an efficient strategy of eukaryotic organisms to quantitatively and qualitatively adapt transcriptional responses after repeated encounters with the initial stimulus (D'Urso & Brickner, 2017). This “transcriptional memory” was initially described in yeast cells that, once fed with galactose instead of glucose, can remember this metabolic challenge and reactivate genes for galactose conversion more rapidly when encountering galactose again (Kundu, Horn, & Peterson, 2007).…”
Section: Transcriptional Memory Enables Learning From Experiencementioning
confidence: 99%